2020
DOI: 10.1186/s12889-020-08461-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sugar-sweetened beverage consumption of Malaysian preschoolers aged 3 to 6 years

Abstract: Background: There is little information about the diet, lifestyle and parental characteristics associated with habitual sugar-sweetened beverage (SSB) consumption in Asian children. The aim of the present study was to assess crosssectional associations between habitual SSB consumption and preschoolers' diet, physical activity, sedentary behaviour as well as parental and child characteristics in Malaysian preschoolers aged 3 to 6 y. Methods: A total of 590 preschoolers, comprising 317 boys and 273 girls were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…The present study showed that caregivers' rates of SSB consumption [24,40] and taking children to fast-food restaurants [41][42][43] frequently were positively associated with SSB consumption among their children, consistent with previous studies at home and abroad. Our study also identified that as low as one-third of caregivers read the NFPs frequently, which was negatively associated with SSB consumption among their children.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that caregivers' rates of SSB consumption [24,40] and taking children to fast-food restaurants [41][42][43] frequently were positively associated with SSB consumption among their children, consistent with previous studies at home and abroad. Our study also identified that as low as one-third of caregivers read the NFPs frequently, which was negatively associated with SSB consumption among their children.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was observed that the most consumed SSB was chocolate malted beverages (data not shown). This is similar to another study where Malaysian preschool children were reported to have flavoured and malted beverages as the most consumed SSB 33 . Next to a high contribution to sugar intake, these flavoured and malted beverages also explain the tendency for children in this study to overconsume dairy products.…”
Section: Discussionsupporting
confidence: 89%
“…Previous researches exactly reported the relationships between SSBs and takeaway dietary patterns ( 25 , 37 , 38 ). Relative fast-food and takeaway environment exposure was positively associated with SSB intake ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%